Impact Of Income Inequality, Economic Growth, and Government Health Expenditure on The Health Sector in Indonesia - Rosalina Tineke Kusumawardhani; Damia Liana (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study investigates the impact of income inequality, regional economic growth, and government health expenditure on the health across 34 provinces in Indonesia from 2018 to 2022. Using a panel data regression with a fixed effects model, the results show that income inequality has a negative and statistically significant effect on the health sector, while economic growth and government spending have positive and significant effects. Provinces with higher income inequality tend to have lower health sector performance, particularly in terms of health budget allocation and public access to health services. In contrast, regions with sustained economic growth and increased government health expenditure experience improvements in health infrastructure and service delivery. These findings suggest that narrowing income disparities and maintaining consistent economic and fiscal support are essential to improving health sector outcomes at the provincial level in Indonesia. Policy interventions focusing on inclusive economic development and equitable budget distribution can help reduce regional disparities in health services.